Characteristics of specialists treating hypothyroid patients: the “THESIS” collaborative - Žarković, Miloš; Attanasio, Roberto; Nagy, Endre V.; Negro, Roberto; Papini, Enrico; Perros, Petros; Cohen, Chagit Adler; Akarsu, Ersin; Alevizaki, Maria; Ayvaz, Göksun; Bednarczuk, Tomasz; Berta, Eszter; et al. (Frontiers in Endocrinology, 2023)
Introduction: Thyroid specialists influence how hypothyroid patients are treated, including patients managed in primary care. Given that physician characteristics influence patient care, this study aimed to explore thyroid specialist profiles and associations with geo-economic factors. Methods: Thyroid specialists from 28 countries were invited to respond to a questionnaire, Treatment of Hypothyroidism in Europe by Specialists: an International Survey (THESIS). Geographic regions were defined according to the United Nations Statistics Division. The national economic status was estimated using World Bank data on the gross national income per capita (GNI per capita). Results: 5,695 valid responses were received (response rate 33•0%). The mean age was 49 years, and 65•0% were female. The proportion of female respondents was lowest in Northern (45•6%) and highest in Eastern Europe (77•2%) (p <0•001). Respondent work volume, university affiliation and private practice differed significantly between countries (p<0•001). Age and GNI per capita were correlated inversely with the proportion of female respondents (p<0•01). GNI per capita was inversely related to the proportion of respondents working exclusively in private practice (p<0•011) and the proportion of respondents who treated >100 patients annually (p<0•01). Discussion: THESIS has demonstrated differences in characteristics of thyroid specialists at national and regional levels, strongly associated with GNI per capita. Hypothyroid patients in middle-income countries are more likely to encounter female thyroid specialists working in private practice, with a high workload, compared to highincome countries. Whether these differences influence the quality of care and patient satisfaction is unknown, but merits further study.